2010
DOI: 10.1002/asjc.166
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic systems implementation with FPGA‐based artificial cell network hardware architectures

Abstract: The cell-based structure, which makes up the majority of biological organisms, offers the ability to grow with fault-tolerance abilities and selfrepair. By adapting these mechanisms and capabilities to nature, scientific approaches have promoted research for understanding related phenomena and associated principles to engine complex novel digital systems and improve their capability. Founded by these observations, the paper is focused on computeraided modeling, simulation and experimental research of embryonic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
0
4
0
2
Order By: Relevance
“…A Kutatóközpontban rendelkezésre áll minden fejlesztéshez szükséges infrastruktúra, hogy FPGA alapú komplex rendszerek kerülhessenek kialakításra [7]. Az IoT térnyerését figyelembe véve az új technológiák irányába is van lehetőség nyitni, ennek keretei között került megtervezésre egy IoT alapú FDM típusú 3D nyomtató is, prototípus alkatrészek gyártására [8].…”
Section: Bevezetőunclassified
See 1 more Smart Citation
“…A Kutatóközpontban rendelkezésre áll minden fejlesztéshez szükséges infrastruktúra, hogy FPGA alapú komplex rendszerek kerülhessenek kialakításra [7]. Az IoT térnyerését figyelembe véve az új technológiák irányába is van lehetőség nyitni, ennek keretei között került megtervezésre egy IoT alapú FDM típusú 3D nyomtató is, prototípus alkatrészek gyártására [8].…”
Section: Bevezetőunclassified
“…A 8. ábrán található osszerak.py elnevezésű Python script volt a leggyakrabban használt formázó script. 7. ábra osszerak.py forráskódja A program Linux parancsokat alkalmazva készít új fájlokat, melyek már a kívánt formát veszik fel.…”
Section: Sed -I 'S/;;/;/g' *Txt 2 Sed -I 'S/;//g' *_texttxt 3 Sedunclassified
“…The proposed bio-inspired system is modeled on a POE-type (Phylogeny, Ontogeny and Epigenesis) embryonic structure, developed in analogy with the evolutionary processes of biological systems [29], [30].…”
Section: The Bio-inspired Control Systemmentioning
confidence: 99%
“…This work is supported by ISRO Satellite Centre, Bangalore. 1 Gayatri Malhotra is Scientist 'SE' in Control Electronics Group (CEG) and has experience of thirteen years. She is pursuing research in bio-inspired electronics.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that there is high possibility that these properties can be implemented on very large scale integrated (VLSI) hardware systems.The research area that leads to new digital system design concept is called as embryonic system design. The cellular embryonic system design of artificial cell network hardware is developed [1] and demonstrates a good example of interaction mechanisms between the cells.…”
Section: Introductionmentioning
confidence: 99%